Takhrij Hadits - Fikri, Shofil; Fitria, Naila Nur; Nurafrizal, Alvin; Maulidi, Mochammad Shoim; Dewantara, Fajar; Oganse, Fatihurrohman (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
Takhrij Hadith is a research method used to research and determine the validity and quality of Hadith sources. This article discusses history, related figures such as ibn al-Kharith, Ya'la ibn 'Atha, Atha' al-Amiri, and Abdullah ibn Amr ibn al-Ash, as well as differences of opinion regarding the validity of Hadith. The data analysis method used is inductive and comparative. Important steps in the Takhrij Hadith process include identifying the Hadith theme, tracing the Hadith, and concluding the results of the Takhrij. The method of takhrij Hadith through the first recitation in the Hadith matan and the first narrator (sanad at the level of sahaba) is also explained. By using books such as al-Jami' ash-Shaghir, Faidh al-Qodir Bi Syarh al-Jami' ash-Shogir, and athraf books, researchers can make it easier to find the Hadith they are looking for. In conclusion, Takhrij Hadith is an important method in understanding the urgency and value of Hadith from various historical and scientific perspectives.